Web-based decision support system for incorporating geosynthetics in coastal protection works - Susana Maria Pereira Garcia (2008)
Geosynthetics are becoming essential components of coastal structures, as there are various possible applications for these materials in coastal defence works. Actually, geosynthetic solutions have been successfully applied in a number of projects around the world, and their use as erosion control measures has shown several capabilities. With the improvements achieved at the level of the materials and the growing interest in the development of innovative techniques of coastal defence, these measures are evolving towards becoming a real alternative to traditional solutions, especially under mild wave climates. Despite the benefits provided by the use of these systems, related to their low cost, simplicity in construction and minimum environmental impacts, there is still a lack of knowledge concerning the design tools and the long term performance, especially under more exposed conditions. Moreover, with respect to the application of geosynthetics in coastal engineering, most of the information is scattered and in most cases it is difficult to have access to all the data required. These issues have prompted the development of a comprehensive Decision Support System (DSS), concerning the incorporation of synthetic fabrics in coastal protection works, with especial emphasis on aspects related to the performance of existing defence structures. The paper will describe a Web-Based DSS, developed as a part of an ongoing research project on the experimental stability analysis of geotextile containers under wave loading, pointing out its requirements, limitations and capabilities. The DSS was developed in PHP and PostgreSQL, with a user-friendly interface, created to facilitate the data access and visualization. This tool aims to improve the decision making process in view of the possible incorporation of synthetic fabrics in coastal protection works as it allows a comprehensive understanding of the feasibility and performance of this kind of solutions.